SKRINING FITOKIMIA DAN UJI AKTIVITAS ANTIDIABETES DARI EKSTRAK ETANOL DAGING BUAH ALPUKAT (Persea americana Mill.) - Simarmata, Yettrie; Manurung, Kesaktian; Harefa, Karnerius; Hasibuan, Mei Sri Rezeki (Jurnal Farmanesia, 2018)
Diabetes mellitus is a set of symptoms that arise in a person characterized by blood glucose levels exceeding normal (hyperglycemia) due to a lack of insulin in the body. One of the medicinal plants that can be used is avocado flesh. This study aims to determine the antidiabetic activity of avocado pulp extract (Persea americana Mill) against male white rats. This study used 25 male white rats divided into 5 groups, namely the negative control group CMC-Na 1%, the positive control group glibenclamide 0.45 mg/kg BW, the EEBA test group at doses of 50, 100, 200 mg/kg BW. The results of the one-way ANOVA analysis of the Tukey HSD test showed that the administration of EEBA at a dose of 100 mg/kg BW and EEBA at a dose of 200 mg/kg BW had a significant difference with a significance value of 0.024 and 0.026 and EEBA at a dose of 50 mg/kg BW had no significant difference with the significance 0.275. Based on the results of the study, it can be concluded that EEBA doses of 50, 100, 200 mg/kg BW have antidiabetic activity.